Association of magnesium intake with type 2 diabetes and total stroke: an updated systematic review and meta-analysis. Issue 3 (19th March 2020) - Zhao, Binghao; Zeng, Lianli; Zhao, Jiani; Wu, Qian; Dong, Yifei; Zou, Fang; Gan, Li; Wei, Yiping; Zhang, Wenxiong
Abstract : Objective: The detailed associations between type 2 diabetes (T2D) and total stroke and magnesium intake as well as the dose–response trend should be updated in a timely manner. Design: Systematic review and meta-analyses. Data sources: PubMed, Embase, Cochrane Library, Web of Science and ClinicalTrials.gov were rigorously searched from inception to 15 March 2019. Eligibility criteria: Prospective cohort studies investigating these two diseases were included. Data synthesis: Relative risk (RR) and 95% CI in random effects models as well as absolute risk (AR) were pooled to calculate the risk of T2D and stroke. Methodological quality was assessed by the Newcastle-Ottawa Scale. Results: Forty-one studies involving 53 cohorts were included. The magnitude of the risk was significantly reduced by 22% for T2D (RR 0.78 (95% CI 0.75 to 0.81); p<0.001; AR reduction 0.120%), 11% for total stroke (RR 0.89 (95% CI 0.83 to 0.94); p<0.001; AR reduction 0.281%) and 12% for ischaemic stroke (RR 0.88 (95% CI 0.81 to 0.95); p=0.001; AR reduction 0.246%) when comparing the highest magnesium intake to the lowest. The inverse association still existed when studies on T2D were adjusted for cereal fibre (RR 0.79; p<0.001) and those on total stroke were adjusted for calcium (RR 0.89; p=0.040). Subgroup analyses suggested that the risk for total and ischaemic stroke was significantly decreased in females, participants with ≥25 mg/m 2 body mass index and those with ≥12-year follow-up; the reduced risk in Asians was not as notable as that in North American and European populations. Conclusions: Magnesium intake has significantly inverse associations with T2D and total stroke in a dose-dependent manner. Feasible magnesium-rich dietary patterns may be highly beneficial for specific populations and could be highlighted in the primary T2D and total stroke prevention strategies disseminated to the public. PROSPERO registration number: CRD42018092690.